Analisis Rasio Keuangan Terhadap Harga Saham Syariah Periode 2015-2024 - Sholikhah, Rofiqoh Mar’atus; Nisa, Thoyibatun; Yunarti, Yuyun (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The growth of investment, particularly in the Islamic capital market sector, plays a significant role in driving the progress of Indonesia's economy. One increasingly popular instrument is Islamic stocks (sharia stocks), which not only offer potential financial returns but also comply with sharia principles. In choosing Islamic stocks as investment objects, investors need to conduct thorough analyses, including paying attention to the company's financial ratios such as liquidity and profitability ratios. The aim of this research is to determine the influence of the Current Ratio, Return on Equity (ROE), and Net Profit Margin (NPM) as measures of Liquidity Ratio and Profitability Ratio on the price of Islamic stocks. The approach used is an associative approach with quantitative data in the form of quarterly financial reports from 2015 to 2024. The data analysis method in this study is conducted using multiple linear regression, accompanied by classical assumption tests, partial tests (t-test), simultaneous tests (F-test), and determination coefficient analysis. Data processing in this research uses SPSS version 26. The results of the study show that partially, Return on Equity (ROE) has a significant positive effect, Net Profit Margin (NPM) has a negative effect, and the Current Ratio has no effect on the price of Islamic stocks. Based on the simultaneous test, the Current Ratio, Return on Equity, and Net Profit Margin significantly affect the price of Islamic stocks at PT Indofood Sukses Makmur Tbk during the 2015–2024 period. The coefficient of determination or the contribution of all independent variables to the Islamic stock price is 93.1%, indicating that the independent variables in this study are able to explain the dependent variable by 93.1%, while the remaining 6.9% is influenced by other factors outside the scope of this research.